Transition animals Care and management - Sah, Rajkumar (Indian Farming, 2018)
The transition period is a critical period in terms of health, production and reproduction in a dairy herd. Regular close monitoring of all things at every aspect is needed for better effectiveness and efficiency of the transition programme. Nutrition and management programmes during this phase directly affect the incidence of post calving disorders, milk production and reproduction in the subsequent lactation. In formulating transition diets, there are three major areas of concern that need to be addressed: healthy liver, rumen adaptation and mineral metabolism. Besides symptomatic treatment of animals, Veterinarians may also consider these facts to reach at final diagnosis.